Horacio Rimoldi J. A. and Scientific Psychology in Latin America - Piñeda, María Andrea; Chavez Bidart, Jorge (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
Focusing on Dr. Horacio Rimoldi, a prominent member of the Interamerican Society of Psychology, this historical study describes the regular circulation of knowledge and training practices that he promoted between universities in Uruguay, the United States, Argentina and Puerto Rico between the early 1950s and 1970. The purpose of these actions was to strengthen the development of psychological science in Latin America at a time when the professionalisation of the discipline was taking place there. A considerable corpus of unpublished sources was recovered, making it possible to analyse more than 160 institutional documents and letters between academics. It describes the courses taught by Rimoldi and his attempts to organise a laboratory at the Universidad de la República de Uruguay, between 1951 and 1952. Also, between 1957 and 1969, collaborations with Universidad Nacional de Córdoba, Universidad de Buenos Aires, CONICET, Universidad de Puerto Rico, Sociedad de Psicología de Puerto Rico and Universidad de Loyola are documented. Dissimilar results were achieved, depending on the complex local contexts and institutional vicissitudes. The interactions highlight processes of professionalization and the constitution of academic centres oriented towards the development of psychology as a basic, autonomous science, close to the natural sciences, which seeks university education focused on research and open to the international agenda.